Salvage chemoradiotherapy with cisplatin and vinorelbine for postoperative locoregional recurrence of non-small cell lung cancer. Issue 47 (November 2017) - Hisakane, Kakeru; Yoh, Kiyotaka; Nakamura, Naoki; Udagawa, Hibiki; Kirita, Keisuke; Umemura, Shigeki; Matsumoto, Shingo; Niho, Seiji; Akimoto, Tetsuo; Tsuboi, Masahiro; Goto, Koichi
Abstract : Abstract: Although a few investigators have demonstrated the effect of concurrent chemoradiotherapy (CRT) for postoperative recurrent non-small cell lung cancer (NSCLC), the outcome of this treatment remains unclear. The aim of this study was to elucidate the efficacy and tolerability of concurrent CRT with cisplatin (CDDP) and vinorelbine (VNR) in patients with postoperative locoregional recurrent NSCLC. A total of 40 patients who had received concurrent CRT with CDDP and VNR between January 1999 and December 2014 were retrospectively analyzed. Patients were treated with CDDP (80 mg/m 2 on day 1) and VNR (20 mg/m 2 on days 1 and 8) every 4 weeks. Radiotherapy was administered concurrently during cycle 1. The delivered x-ray radiation dose was 60 Gy in all 37 patients who received x-ray radiotherapy; 3 patients received proton beam radiation (66 Gy [RBE] in 1 patient and 60 Gy [RBE] in 2 patients). The objective response rate was 85% (95% confidence interval [CI], 70.9%–92.9%). The median progression-free survival was 20.3 months (95% CI, 12.9 months–not reached). The 2-year survival rate was 78.9% (95% CI, 63.0%–89.1%). The most common grade ≥3 toxicity was neutropenia (18%). No grade ≥3 radiation pneumonitis and no treatment-related deaths were observed. Our study revealed that concurrent CRT with CDDP and VNR was active and safe for patients with postoperative locoregional recurrent NSCLC. Salvage CRT for postoperative locoregional recurrent NSCLC might be a promising treatment for selected patients.